Beyond the “Critical” Curtain: Community-based Service Learning in an African Context - West, Gerald O. (Teaching theology and religion, 2004)
A case of community-based service learning in the School of Theology at the University of Natal, Pietermaritzburg, South Africa is analyzed for what it means to teach biblical studies in an African context where biblical scholarship is partially constituted by ordinary African readers of the Bible and where context is a central pedagogical concept. Reflecting on a series of experiments over the past ten years in two second-year University level modules, the article analyzes the contours of a partnership between the academy and local communities of the poor, working-class, and marginalized through community-based service learning. This partnership provides a form of contextualization that enables students to integrate the forms of engagement with the Bible they bring to their formal theological studies and the forms of critical distance that characterize the discipline of biblical studies.